Institutional quality and livestock production in post-soviet countries: Three essays - Rustam Rakhmetov (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2024)
An inclusive institutional environment is vital for the livestock industry's success, enhancing animal health, food security, trade, and economic resilience. This dissertation examines the institutional factors shaping livestock performance in post-Soviet countries, focusing on the transition to market-oriented systems. A new metric evaluates the quality and enforcement of meat market regulations, revealing discrepancies between official policies and practical implementation. Panel data analysis highlights a non-linear relationship between corruption control and livestock productivity, varying across organizational structures. The micro-level analysis underscores the role of institutional infrastructure in integrating producers into formal markets while revealing that production growth may push smaller farmers into informal markets. Findings emphasize the importance of the institutional environment to support livestock industry transformation and market integration. – – Ein inklusives institutionelles Umfeld ist entscheidend für den Erfolg der Viehwirtschaft, da es Tiergesundheit, Ernährungssicherheit, Handel und Stabilität stärkt. Diese Dissertation untersucht die institutionellen Faktoren, die die Viehwirtschaft in postsowjetischen Ländern prägen, mit Fokus auf den Übergang zu marktorientierten Systemen. Eine neue Metrik bewertet Qualität und Durchsetzung von Fleischmarktregulierungen und zeigt Lücken zwischen Vorgaben und Umsetzung. Die Paneldatenanalyse zeigt eine nichtlineare Beziehung zwischen Korruptionskontrolle und Produktivität, abhängig von Strukturen. Die Mikroanalyse betont die Rolle institutioneller Infrastruktur für die Integration von Produzenten in formelle Märkte und zeigt, dass Produktionswachstum kleinere Landwirte in informelle Märkte drängen kann. Ergebnisse unterstreichen die Bedeutung institutioneller Umfeld für Transformation und Marktintegration.
urn:nbn:de:gbv:3:4-1981185920-1202329
Keywords: 330